2015
DOI: 10.4085/1062-6050-49.5.04
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Anti-Inflammatory Drug Use and Endurance During Running in Male Long-Distance Runners

Abstract: Context: The effect of ibuprofen on pain tolerance during exercise is controversial, and its effects on endurance performance have been poorly investigated.Objective: To investigate the effect of prophylactic administration of the nonsteroidal anti-inflammatory drug ibuprofen on the time until the self-report of fatigue (t lim ) in runners with exercise-induced muscle damage.Design ). Intervention(s): Participants were assigned to 2 groups (ibuprofen group ¼ 10, placebo group ¼ 10) to perform t lim trials (spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 31 publications
1
22
0
1
Order By: Relevance
“…Cleak, & Eston. 1992;Da Silva et al 2015;Nosaka & Clarkson, 1996;Tokmakdis et al 2003), we cannot exclude that peripheral factors that were not assessed in the current study, such as inflammation and/or alterations to muscle metabolism, may have contributed to the ergogenic effect of ACT. Moreover, due to the nature of cycling exercise, it is technically challenging to directly test cortical alterations via changes to voluntary activation using the interpolated twitch technique (Doyle-Baker et al 2017).…”
Section: Neuromuscular Functionmentioning
confidence: 84%
“…Cleak, & Eston. 1992;Da Silva et al 2015;Nosaka & Clarkson, 1996;Tokmakdis et al 2003), we cannot exclude that peripheral factors that were not assessed in the current study, such as inflammation and/or alterations to muscle metabolism, may have contributed to the ergogenic effect of ACT. Moreover, due to the nature of cycling exercise, it is technically challenging to directly test cortical alterations via changes to voluntary activation using the interpolated twitch technique (Doyle-Baker et al 2017).…”
Section: Neuromuscular Functionmentioning
confidence: 84%
“…However, our findings in the current study are in line with some previous observations that IBP ingestion does not improve performance during whole body exercise in humans (e.g., Cleak, & Eston. 1992;Da Silva et al 2015;Nosaka & Clarkson, 1996;Tokmakdis et al 2003). Previous studies that have reported improved exercise performance following IBP administration have typically assessed exercise performance following muscle damage.…”
Section: Effects Of Acute Ibp Ingestion On Exercise Performancementioning
confidence: 99%
“…Previous studies that have reported improved exercise performance following IBP administration have typically assessed exercise performance following muscle damage. Nonetheless, while there is some evidence to suggest that the increases in muscle soreness, pain, damage and contractile dysfunction after contraction-induced muscle damage can be attenuated following NSAID administration (Ebbeling & Clarkson, 1989;Hasson et al 1993;Pizza et al 1999;Tokmakdis et al 2003), there is also evidence that NSAID administration does not impact these variables after muscle damage is induced (Da Silva et al 2015;Tokmakdis et al 2003). Taken together, these observations suggest that the ergogenic potential of administering IBP, a purported analgesic and anti-inflammatory agent (Friden & Lieber, 1992), is limited without prior induction of muscle damage, and even when muscle damage is induced, and inflammation and pain sensation are correspondingly increased, the effect of IBP ingestion on exercise performance is equivocal.…”
Section: Effects Of Acute Ibp Ingestion On Exercise Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Eine Studie hingegen zeigt sogar eine vermehrte Muskelhypertrophie unter Ibuprofen-oder Paracetamol-Therapie (39). Eine Studie hinsichtlich der Ausdauerleistungsfähigkeit von Langstreckenläufern zeigte keinen ergogenen Effekt einer NSAR-Therapie (40). Hingegen wurde berichtet, dass schwere medizinische Komplikationen (Nierenversagen, gastrointestinale Blutungen, Myokardinfarkte) bei Marathonläufern vor allen bei denjenigen auftreten, die NSAR, oft in hoher Dosierung, eingenommen hatten (41).…”
Section: Nichtsteroidale Antirheumatikaunclassified